KARAKTERISASI TOXOPLASMA GONDII ISOLAT INDONESIA - Chandra Yowani, Sagung; Kumolosasi, Endang; Singgih Wibowo, Marlia (Jurnal Kimia (Journal of Chemistry), 2012)
Cathodic protection basically reduces the corrosion rate of a metallic structure by reducing its corrosion potential, Toxoplasma gondii isolated from diaphragm of sheep at an abbatoir in Sukabumi, West Java had been characterized by Centre Research Institute for Animal Sciences. The characterization included study of morphology by optical microscope, study of ultrastructure by transmission electron microscope, the study of the parasite growth in mice Mus musculus, and study of proteins of the parasite. The growth of parasite in mice had been studied using two groups of mice i.e., normal group and immunosuppressed group. The number of parasites was compared statistically using student’ t-pair test. Results showed that dexamethasone at a dose of 5.2 mg/20 g body weight intra peritoneally to the immunosuppresed mice did not increase the number of extracelluler parasites in the peritoneal fluid. The best parasite harvest time was on the 4th day after inoculation. Determination of parasite protein obtained at 4 days after inoculation using sodium dodecyl sulphate polyacrylamide gel electrophoresis showed a dominant surface protein of 42 kDa.
Keywords: characterization, Toxoplasma gondii, local isolate